Phytochemicals analysis of Arum palaestinum extracts and their antibacterial effect against Pseudomonas syringae pv. tomato (Pst) - Ghaith, Samaher; Shahine, Dany Abi; Fayad, Antoine Abou; Afram, Michel; Borjac, Jamilah (Edelweiss Applied Science and Technology, 2025)
Arum palaestinum is a traditional medicinal wild plant indigenous to the Levant. The present study explores its phytochemical constituents and antibacterial activity in agriculture to control and inhibit the growth of Pseudomonas syringae pv. tomato (Pst). Aqueous, ethanolic, and chloroform extracts of the dried leaves, flowers, and rhizomes were prepared at a final concentration of 50 mg/mL. HPLC-MS analysis of A. palaestinum extracts revealed the presence of 13 previously characterized compounds and 2 new ones. Using the disc diffusion method and compared to ciprofloxacin and copper oxychloride that were used as controls, the aqueous extracts of the leaves, flowers, and rhizomes exhibited significant inhibition against P. syringae with high inhibition zones (IZDs). Based on the broth dilution method, the aqueous extracts possessed the greatest antimicrobial effect against P. syringae, followed by the ethanolic extracts, which showed a moderate antimicrobial effect for each part. In the field, the aqueous and ethanolic extracts controlled and eradicated the speck disease on tomato better than the chloroform extracts. Therefore, A. palaestinum can be used as an alternative to control bacterial speck disease and deserves to be further studied in organic agriculture.